Effect of phosphorus application rate on Mentha spicata L. grown in deep flow technique (DFT) - Chrysargyris, Antonios (2019)
The present study evaluated the impact of phosphorus application rate on plant growth and physiological parameters, antioxidant activity, chemical composition, and essential oil yield and composition of hydroponically grown spearmint plants. Increased P levels resulted in high dry matter content of the aerial part. Antioxidant activity of spearmint leaves was significantly higher at the highest P levels. Although essential oil yield was not affected, essential oil composition varied among the studied P levels, especially carvone content. Total and individual organic acids content was higher when 50 mg/L P were added in the nutrient solution. Rosmarinic acid was the main detected phenolic compound, while the highest total phenolic compounds and rosmarinic acid content was observed at 50 and 70 mg/L of P, respectively. In conclusion, phosphorus application rate may affect spearmint growth and development, as well as chemical composition and essential oil composition.